Taxation:Depth Classification Version of CC - Neelameghan, A. (Journal of Information and Knowledge, 1971)
A depth classification version of Colon Classification for compound subjects going with the Basic Subject "x72 Taxation" is given. The methodology of design is based on that for freely faceted classification. Economy in schedule building' has been achieved by using different devices-such as, Subject Device and Divide-like Device-wherever found helpful. An index to the schedule, fifty-four examples of micro documents classified according to the depth version, and an alphabetical index to the subjects of the micro documents derived by chain procedure, are given.